EKSISTENSI WANITA DALAM PERSPEKTIF ISLAM - Efendi, Aprijon (MUWAZAH, 2013)
Abstract : Women have a vital role for the welfare of the community, both on a small scale such as family formation and in such large-scale development of the country. Islam asserts that, the identity of a nation with close ties to the role of women, even the existence of a benchmark for the success of women of the country, if a woman becomes both, then the country will go forward, otherwise if she does not act well then the country will be destroyed. Although women have made significant contributions in development, but the role of women has not been proportional to the number of existing female population. Currently various problems still disturbing existence of women in society. To overcome these authors offer some views, such as relocating back function submit completely to the woman and the woman herself, but still adhere to the instructions of the Qur'an and Hadith. Abstrak : Perempuan memiliki peran penting bagi kesejahteraan masyarakat, baik dalam skala kecil seperti pembentukan keluarga dan dalam pembangunan skala besar seperti negara. Islam menegaskan bahwa, identitas bangsa memiliki hubungan dekat dengan peran perempuan, bahkan keberadaan tolok ukur keberhasilan perempuan dari negara, jika seorang wanita menjadi baik, maka negara akan maju, sebaliknya jika dia tidak tidak bertindak dengan baik maka negara akan hancur. Meskipun perempuan telah memberikan kontribusi yang signifikan dalam pembangunan, namun peran perempuan belum sebanding dengan jumlah penduduk perempuan yang ada. Saat ini berbagai masalah masih mengganggu keberadaan perempuan dalam masyarakat. Untuk mengatasi penulis ini menawarkan beberapa pandangan, seperti relokasi kembali fungsi menyerahkan sepenuhnya kepada wanita dan wanita itu sendiri, namun tetap mematuhi instruksi dari AlQur'an dan Hadis.